Sistem Deteksi Dini dan Pemadaman Kebakaran Otomatis di Rumah Berbasis IoT Menggunakan NodeMCU ESP32 - Saputra, Dimas Bagus; Hidayati, Rahmi; Suhardi, Suhardi (Jurnal Sistem Komputer dan Informatika (JSON), 2024)
Fire is a serious disaster that causes significant losses in terms of both material assets and loss of life, especially in densely populated residential areas. Fires that occur in one house can easily spread to other houses. To prevent this issue, an early fire detection and automatic fire suppression system has been developed for homes based on the Internet of Things (IoT) using NodeMCU ESP32. This system has the ability to detect early signs of fire, gas, and temperature conditions, and takes automatic action when potential fire hazards are detected. Additionally, the system sends real-time push notifications to users' Android applications to provide warning messages. Test results indicate that the fire sensor can detect flames up to a distance of 130 cm with an average notification delay of approximately 2,37 seconds. The MQ-2 gas sensor can detect butane gas up to a distance of 170 cm with an average notification delay of about 2,84 seconds, while the DHT22 temperature sensor has an average accuracy of approximately 98,52% with a notification delay of about 2,03 seconds.